Vidros e vitrocerâmicas contendo óxido de nióbio para dispositivos luminescentes - Marcondes, Lia Mara Silva (2019)
Niobium germanate glasses and nanocrystalline glass-ceramics were obtained with good optical quality and wide transparency window. Undoped (90-x)GeO2-xNb2O5-10K2O glasses are formed with the addition of up to 20 mol% of Nb2O5. In glasses with high niobium content the formation of NbOx clusters in the germanate network was identified. Eu3+-doped, Er3+-doped and Er3+/Yb3+-codoped GeO2-Nb2O5-K2O glasses varying the concentration of Nb2O5 were also manufactured. In general, addition of Nb2O5 in the host may alter the photoluminescent properties of the material such as the increase in the photoluminescence quantum efficiency and the broadband around 1.5 μm in the Er3+-doped samples. For this reason, Eu3+-doped, Er3+-doped and Er3+/Yb3+-codoped GeO2-Nb2O5-K2O glasses-ceramics with 15 mol% Nb2O5 were synthesized. K2Nb14O36 phase was identified in the glass-ceramic samples obtained by heat treatment. The photoluminescent properties were modified in glass ceramics with complete crystallization (20 hours of heat treatment) in relation to the precursor glass. This behavior occurs due to the insertion of the rare-earth ions in the nanocrystal that alters the strength of the crystalline field around the ions and allows an adequate interaction between them. Finally, GeO2-Nb2O5-K2O glass and glass-ceramic samples doped with up to 2,0 mol% of Er2O5 were prepared. High erbium contents exhibited strong enhancement of upconversion emission and the erbium content allowed a visible tunable phosphor emitting either red-to-green light. Thus, rare-earth-doped niobium germanate glass and glass-ceramic are candidates for photonics application, such as optical amplifiers, visible and NIR lasers.